Veterinary medicine in the public health: approach in one health of the pandemic of covid-19 - Cavalcanti, Ricardo Vinícius Duarte (2020)
Public health, as a segment of veterinary science, provokes a reflection on the integration of professional health sectors. This approach is called One Health, which has got stronger in countries around the world. The COVID-19 pandemic has been a promoter of the adaptations of science and public policies, seeming to show points of failure in the health system as it is currently constituted and structured. In this sense, it is asked whether greater participation of veterinary medicine, as a component of public health, could contribute to mitigating the effects of COVID-19. Through exploratory research, a bibliographic review is designed to strengthen the theoretical discussion. The research was carried out on Descritores em Ciência da Saúde (DeSC); followed by a bibliographic survey on data platforms: ScienceDirect, BVS (Biblioteca Virtual em Saúde), Periódicos Capes and complementary information at the Federal Council of Veterinary Medicine of Brazil and the Center for Disease Control and Prevention in the United States. A search for indexed scientific articles was carried out in the last 10 years, considering the database. Academic articles in Portuguese and English were selected for the development of this research, counting 101 original review articles and case reports in English and Portuguese. In the second stage, among the abstracts raised, a selection was made of those that included at least 2 keywords and whose formulation was equal to or similar to the research proposal carried out for this study, followed by rigorous content analysis to verify adherence to the proposed theme. As a result, it is envisaged that using the structured system in the idea of ​​One Health, different impacts concerning the pandemic could have been obtained.